Penggunaan Bebat Perineum (Kempitan) Untuk Mengurangi Nyeri Luka Perineum Pada Ibu Post Partum - Dewi Susilowati; Triwik Sri Mulati (Poltekkes Kemenkes Surakarta, 2018)
Abstract: Perineal Bandage, Maternal Perineal Wound Pain. The purpose of this study to prove the effect of perineal bandage to reduce pain in the perineal wound. The research design was quasi experiment with untreated control group design with pretest and posttest samples: some post partum mother who suffered wounds perineum in BPM Klaten some 91 people. Bivariate data analysis using statistical test used is t –test. Results from this study is that the bandage perineum (kempitan) is effective for reducing maternal perineal wound pain post partum compared to the control group who were given regular perineal wound treatment but without being given a dressing perineum.